Pengaruh Profitabilitas, Struktur Modal, Dan Likuiditas Terhadap Nilai Perusahaan - Calvin Febri Yanto, Jonardi (Jurnal Paradigma Akuntansi, 2021)
The aim of this research is to examine the empirical evidence of profitability, capital structure, and liquidity on firm value in manufacturing companies listed in Indonesia Stock Exchange. This research used 61 listed manufacturing companies that were selected using purposive sampling method, during the research period 2014 until 2018. Data were analyzed using purposive sampling method. The result of the research indicates that profitability have a positive significant effect on firm value, capital structure have no significant effect on firm value, and liquidity have a negative significant effect on firm value.